The potential of rambutan honey toothpaste in reducing the dental plaque index: a quasi Experimental study - Yuslianti, Euis Reni; Ningrum, Anindya Sekar Ayu; Endrowahyudi, Hartanto (Universitas Padjadjaran, 2023)
ABSTRACTIntroduction: The accumulation of dental plaque is a common cause of dental and oral health problems such as caries and periodontitis, therefore it is necessary to control plaque. Brushing is the most effective way to control plaque. Currently, there are various toothpastes used by the people, one of which is herbal toothpaste. One of the herbal toothpastes that has an antibacterial potential is rambutan honey toothpaste. The purpose of this study was to analyze the effectiveness of rambutan honey toothpaste in reducing the dental plaque index. Methods: this research was Quasi Experimental design research with a pre-test post-test control group design. The twenty samples were divided into three treatment groups, namely the group that brushed teeth with base toothpaste, rambutan honey toothpaste, and aquadest. All samples were asked to brush their teeth using base toothpaste, rambutan honey toothpaste, and aquadest twice, after using toothpaste for one day, the plaque index was measured by the Silness and Loe method. Data were analyzed using Kruskal-Wallis and post hoc Mann-Whitney tests (p<0.05). Results: There was a significant difference between the plaque index score before and after using rambutan honey toothpaste with a p value=0.005 (p≤0.05). The results also showed the effect of brushing teeth with base toothpaste, rambutan honey toothpaste, and aquadest on plaque index with a value of p=0.005 (p≤0.05). The results showed that there was no significant difference in dental plaque index between base toothpaste and rambutan honey toothpaste with a p value=0.583. Conclusion: Rambutan honey toothpaste has a potential in reducing the dental plaque index.Keywords: plaque index, rambutan honey, toothpaste